Complications of obesity in children and adolescents during covid-19 pandemic: A narrative review - Concepción-Zavaleta, Marcio (2021)
Background: Obesity in children and adolescents has increased exponentially around the world. Furthermore, the COVID-19 pandemic has led to a higher pediatric obesity rate. The excess adipose tissue generates a dysregulation of adiponectin, ghrelin, and leptin, among others. Metabolic alterations can develop cardiovascular disease, dyslipidemias, arterial hypertension, type 2 diabetes mellitus, nonalcoholic fatty liver disease, sleep disorders, and higher risk of COVID-19 severity. Obesity has different therapeutic approaches such as behavioral weight loss programs, pharmacologic treatments, and surgical procedures. Therefore, timely diagnosis and treatment are important to decrease the mortality in obesity among pediatric population.